2018
DOI: 10.21577/0103-5053.20180069
|View full text |Cite
|
Sign up to set email alerts
|

Burkholderia thailandensis: the Main Bacteria Biodegrading Fipronil in Fertilized Soil with Assessment by a QuEChERS/GC-MS Method

Abstract: Due to the expansion of sugarcane crops and the high costs of agricultural inputs, an alternative for fertilization of the soil is the use of humic substances (HS) because they improve its physical-chemical properties. The objective of this study was to assess the biological degradation of fipronil in soil supplemented with HS. For determination of fipronil and its metabolites, we validated a quick, easy, cheap, effective, rugged, and safe gas chromatography-mass spectrometry (QuEChERS/GC-MS) method, which yie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 26 publications
(30 reference statements)
0
11
0
Order By: Relevance
“…To date, only a few studies on fipronil biodegradation have been conducted. 1,18,24,[33][34][35][36]38,41 Furthermore, only Paracoccus sp., 1 B. thuringiensis, 29 B. firmus, 39 Stenotrophomonas acidaminiphila, 41 Burkholderia thailandensis, 32 Staphylococcus arlettae, Bacillus thuringiensis, 37 Streptomyces rochei strain AJAG7, 58 and Bacillus sp. 33 have been studied for the degradation of fipronil.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…To date, only a few studies on fipronil biodegradation have been conducted. 1,18,24,[33][34][35][36]38,41 Furthermore, only Paracoccus sp., 1 B. thuringiensis, 29 B. firmus, 39 Stenotrophomonas acidaminiphila, 41 Burkholderia thailandensis, 32 Staphylococcus arlettae, Bacillus thuringiensis, 37 Streptomyces rochei strain AJAG7, 58 and Bacillus sp. 33 have been studied for the degradation of fipronil.…”
Section: Resultsmentioning
confidence: 99%
“…It is important to note that, in other published work, the biodegradation of fipronil usually also produced fipronil-sulfide and fipronil-sulfone. 27,32,41 The presence of the other two metabolites 5 is related more to environmental influences.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Among them, we can mention Bacillus thuringiensis [ 57 ] and Streptomyces rochei [ 58 ]. In the same vein, Cappelini et al [ 59 ] observed that the bacterium Burkholderia thailandensis belonging to the phylum Proteobacteria also showed potential for fipronil degradation. Another example is the result observed by Ahemad et al [ 60 ], where the authors stated that the Rhizobium strain MRL3 could grow in a medium with fipronil as the sole source of carbon and nitrogen.…”
Section: Discussionmentioning
confidence: 95%
“…Productivity of sugarcane crops is maintained by soil management, such as addition of organic matter and nutrients, through the use of vinasse and filter cake, maintenance of sugarcane straw on the soil surface, crop rotation, development of new cultivars and use of pesticides (Bordonal et al, 2018). Due to restrictions of the use of organochlorine and organophosphate insecticides, the application of fipronil is increasing (Cappelini et al, 2018). This insecticide is applied in sugarcane plantation as Regent® 800 WG to control Lepidoptera and Orthoptera on crops and Coleoptera larvae in soils.…”
Section: Introductionmentioning
confidence: 99%